The WOM Effect to Perceived Justice, Satisfaction and Repurchase Intentions - Hariyadi Tri Wahyu Putra (Business and Entrepreneurial Review, 2007)
The background of this research focused on complaint management in catering service in Jakarta, thus focused on justice or fairness theory to explain satisfaction with the complaint handling process with post complaint customer behaviour such as word of mouth (WOM) or repurchase intentions.  The objective (s) of this research was to examine the impact of WOM as mediating variable to perceived fairness, satisfaction, and repurchase intentions. This will hopefully. shed some more light on the post complaint customer behavior process especially in catering service. Data analysis in this research used Structural Equation Model (SEM) with AMOS 4.0 software. Perceived fairness would have a positive effect on satisfaction, but would not have a positive effect on WOM valance and repurchase intentions. Perceived fairness would have a negative effect on WOM dissemination. WOM valance would have a positive effect on repurchase intentions, but would not on satisfaction. WOM dissemination would have a negative effect on satisfaction and WOM valance. but would not significantly on repurchase intentions. Satisfaction would not always have a positive effect on repurchase intentions.